Protein succinylation: regulating metabolism and beyond - Hou, Xiaoli; Chen, Yiqiu; Li, Xiao; Gu, Xianliang; Dong, Weixia; Shi, Jie; Ji, Shaoping (Frontiers in Nutrition, 2024)
Modifications of protein post-translation are critical modulatory processes, which alters target protein biological activity，function and/or location, even involved in pathogenesis of some diseases. So far, there are at least 16 types of post-translation modifications identified, particularly through recent mass spectrometry analysis. Among them, succinylation (Ksuc) on protein lysine residues causes a variety of biological changes. Succinylation of proteins contributes to many cellular processes such as proliferation, growth, differentiation, metabolism and even tumorigenesis. Mechanically, Succinylation leads to conformation alteration of chromatin or remodeling. As a result, transcription/expression of target genes is changed accordingly. Recent research indicated that succinylation mainly contributes to metabolism modulations, from gene expression of metabolic enzymes to their activity modulation. In this review, we will conclude roles of succinylation in metabolic regulation of glucose, fat, amino acids and related metabolic disease launched by aberrant succinylation. Our goal is to stimulate extra attention to these still not well researched perhaps important succinylation modification on proteins and cell processes.